Determinant Factors Affecting the Number of Tourist Visits to Gili Trawangan, North Lombok - Iwan Harsono; Ahmad Jouhari; Neelu Seetaram; Amitesh Kumar Singh (Tinta Emas Publisher, 2024)
This research aims to determine the effect of tourist income, travel time, travel costs on the number of tourist visits to Gili Trawangan. Data collection was carried out using primary data (questionnaires) which were filled out by visitors to tourist attractions on Gili Trawangan. Data processing uses classical assumption tests (normality test, reliability test, heteroscedasticity test, multicollinearity test), multiple linear regression and hypothesis testing. The research results show that the coefficient of determination (R2) is 0.72. The research results simultaneously show that tourist income, travel time, travel costs and attractiveness have a significant effect on the number of tourist visits. The research results show that partially income, travel time, travel costs and attractiveness have a significant effect on the number of tourist visits. It is hoped that tourist attraction managers will continue to innovate so that they always have attractions that can make tourists come back to tourist attractions on Gili Trawangan.